2019
DOI: 10.3390/molecules24234222
|View full text |Cite
|
Sign up to set email alerts
|

Bixa orellana L. (Bixaceae) and Dysphania ambrosioides (L.) Mosyakin & Clemants (Amaranthaceae) Essential Oils Formulated in Nanocochleates against Leishmania amazonensis

Abstract: Leishmaniasis is a group of neglected tropical diseases caused by protozoan parasites of the Leishmania genus. The absence of effective vaccines and the limitations of current treatments make the search for effective therapies a real need. Different plant-derived essential oils (EOs) have shown antileishmanial effects, in particular from Bixa orellana L. (EO-Bo) and Dysphania ambrosioides (L.) Mosyakin & Clemants (EO-Da). In the present study, the EO-Bo and EO-Da, formulated in nanocochleates (EO-Bo-NC and EO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Quinoline-derivative molecules have shown antileishmanial activity in both in vitro and/or in vivo experiments against different Leishmania spp., such as L. amazonensis, L. mexicana, and L. donovani, among others [11,17,24]. However, when used to treat infected mice, high daily doses (between 10 and 50 mg per kg body weight) are usually administered to the animals [32,42,47]. Here, we reported the in vivo efficacy of ICHQ/Mic against L. infantum infection by using 5.0 mg of ICHQ per kg body weight.…”
Section: Discussionmentioning
confidence: 94%
“…Quinoline-derivative molecules have shown antileishmanial activity in both in vitro and/or in vivo experiments against different Leishmania spp., such as L. amazonensis, L. mexicana, and L. donovani, among others [11,17,24]. However, when used to treat infected mice, high daily doses (between 10 and 50 mg per kg body weight) are usually administered to the animals [32,42,47]. Here, we reported the in vivo efficacy of ICHQ/Mic against L. infantum infection by using 5.0 mg of ICHQ per kg body weight.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding the antibacterial effect, we observed that BoEA and ElAc exerted bactericidal effects. The antimicrobial activity of BoEA has been reported previously against various microorganisms, such as Gram-positive bacteria ( S. aureus and S. pyogenes ) [ 18 ], Gram-negative bacteria (Escherichia coli , Salmonella typhi , Shigella dysenteriae , Klebsiella pneumoniae , Proteus vulgaris ) [ 37 ], yeast ( Candida albicans ) [ 38 ], antileishmanial [ 39 ], and antimalarial activities [ 40 ]. Our group previously demonstrated that BoEA has antimycobacterial activity against Mabs [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hunt for effective therapeutics to treat Leishmaniasis has become an urgent requirement due to the absence of effective medicines and the limits of present treatments ( Machín et al, 2019 ). The anti-leishmanial activity of D. ambrosioides was demonstrated by Monzote et al, 2014 and 2018 ( Monzote et al, 2014 ; Monzote et al, 2018 ) against amastigotes and promastigotes of Leishmania amazonensis.…”
Section: Health Benefitsmentioning
confidence: 99%